Advanced neurological monitoring. Issue 2 (February 2016) - Ralph, James; Singh, Naginder
Abstract: There is evidence that the secondary insults of reduced cerebral perfusion and oxygenation are directly correlated with poor neurological outcomes, particularly after traumatic brain injury (TBI) and subarachnoid haemorrhage (SAH). Several advanced neurological monitoring modalities are available, some are in routine use and others remain research tools. They allow measurement of global and regional variables including pressure, flow, oxygenation and the concentration of metabolites. Close monitoring of traditional systemic variables combined with advanced neurological monitoring can provide early detection of secondary insults and allow early goal directed interventions to improve outcomes.